Thoughtful Snooping: Agency, Affect and the Walking Simulator - MacKeil, Sarah (Loading)

(untitled) (Canadian Game Studies Association, 2024)
In the past decade, “walking simulator” has evolved from an insult to a critically and commercially successful genre of games. Through subversive mechanics and an emphasis on immersive, affective storytelling, these games are well-situated to explore LGBTQ+ narratives and queer forms of play (Ruberg, 2019). This paper unpacks the affective implications of games that urge the player to “snoop around” personal spaces, including Gone Home (Fullbright, 2013), What Remains of Edith Finch (Giant Sparrow, 2017), and A Normal Lost Phone (Accidental Queens, 2017). After a broad overview of the genre and relevant scholarship, the author examines the emotional impact of ludic “snooping”. Specifically, the author considers how games centring this mechanic simulate intimacy (while problematizing consent), engage agency through interaction and movement, and harness a disorienting atmosphere in their storytelling. Finally, the paper reflects on how character identification can be understood in the context of “games for change”, so-called empathy games, and the need to move towards a more thoughtful engagement with queer affect. This paper touches on each of these issues with a broad, interdisciplinary approach rooted in rhetoric, close reading, and queer theory.